Traditional Uses, Phytochemistry, Pharmacology, and Quality Control of Dendrobium officinale Kimura et. Migo - Chen, Wenhua; Lu, Jiemiao; Zhang, Jiahao; Wu, Jianjun; Yu, Lilong; Qin, Luping; Zhu, Bo (Frontiers in Pharmacology, 2021)
Dendrobium officinale, a well-known plant used as a medicinal and food homologous product, has been reported to contain various bioactive components, such as polysaccharides, bibenzyls, phenanthrenes, and flavonoids. It is also widely used as a traditional medicine to strengthen “Yin”, nourish heart, tonify five viscera, remove arthralgia, relieve fatigue, thicken stomach, lighten body, and prolong life span. These traditional applications are in consistent with modern pharmacological studies, which have demonstrated that D. officinale exhibits various biological functions, such as cardioprotective, anti-tumor, gastrointestinal protective, anti-diabetes, immunomodulatory, anti-aging, and anti-osteoporosis effects. In this review, we summarize the research progress of D. officinale from November 2016 to May 2021 and aim to better understand the botany, traditional use, phytochemistry, and pharmacology of D. officinale, as well as its quality control and safety. This work presents the development status of D. officinale, analyzes gaps in the current research on D. officinale, and raises the corresponding solutions to provide references and potential directions for further studies of D. officinale.